2015
DOI: 10.1371/journal.pone.0138504
|View full text |Cite
|
Sign up to set email alerts
|

E. adenophorum Induces Cell Cycle and Apoptosis of Renal Cells through Mitochondrial Pathway and Caspase Activation in Saanen Goat

Abstract: The cytotoxicity effects of E. adenophorum on cell cycle and apoptosis of renal cells in Saanen goat was evaluated by TUNEL, DAPI, AO/EB staining, DNA fragmentation assay, Caspase activity, Western-blot, qRT-PCR and flow cytometry analysis. 16 saanen goats randomly divided into four groups were fed on 0%, 40%, 60% and 80% E. adenophorum diets. The Results showed that E. adenophorum induced typical apoptotic features of renal cells. E. adenophorum significantly suppressed renal cells viability, caused cell cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 42 publications
3
13
0
Order By: Relevance
“…Previous studies showed that the ingestion of A. adenophora as a feed additive induced hepatotoxicity in mice 28 and rat 7 , as well as chronic pulmonary disease in horses 29 . In our previous studies, apoptosis pathway was triggered by A. adenophora in goat and mice 10 , 30 , 31 . In this study, IL-1β, a pro-inflammatory cytokine, was induced by A. adenophora (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies showed that the ingestion of A. adenophora as a feed additive induced hepatotoxicity in mice 28 and rat 7 , as well as chronic pulmonary disease in horses 29 . In our previous studies, apoptosis pathway was triggered by A. adenophora in goat and mice 10 , 30 , 31 . In this study, IL-1β, a pro-inflammatory cytokine, was induced by A. adenophora (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…p53 also advances apoptosis through the mitochondrial pathways ( 30 ). The p53-dependent apoptosis leads to mitochondrial apoptotic changes via activation of the Bax and caspases cascade ( 31 ). Furthermore, p53 activates the p21 protein to instigate a the G1 phase cell cycle arrest ( 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…Cellular morphological changes were subsequently examined using fluorescence microscopy; live cells were stained green, apoptotic cells, yellow and necrotic cells, red. The percentage of apoptotic cells was calculated using the following formula: Apoptotic rate (%)=(number of apoptotic cells/total number of cells)x100, as previously described (17,18).…”
Section: A549 Cell Culturementioning
confidence: 99%